When tax practitioners file their personal tax returns: Do attitude, social norms, and perceptual control matter? / Siti Nurfarhana Mohamad Dzulkifli and Seri Ayu Masuri Md Daud - Mohamad Dzulkifli, iti Nurfarhana; Md Daud, Seri Ayu Masuri (Universiti Teknologi MARA, 2021)
Tax revenue is a key source of income for most countries in the world. To maximize tax revenue, it is critical that taxpayers comply with relevant tax laws particularly in a self-assessment filing system. Alas, many countries are still grappling with tax evasion or even tax avoidance issue. A key challenge is tax compliance behavior remains a complex and perplexing topic. While a lack of tax knowledge is pertinently attributable to unintentional non-compliance, the causes of intentional non-compliance are far from clear. This study aims to investigate the factors associated with intentional tax non-compliance by ruling out the variation in tax knowledge explanation. In so doing, this study employs a sample of respondents deemed conversant with tax knowledge. More specifically, this study surveys 104 tax practitioners in Malaysia using a convenience sampling technique and utilizes the theories of planned behavior and free trait to explore how they behave when filing their personal tax returns. The findings suggest only subjective norms is significantly linked to their tax compliance behavior. This study extends the literature on the role of individual factors on tax compliance behavior among tax practitioners acting in a different persona.